Fürstliches Arkadien Sommerresidenzen im 18. Jahrhundert - Leopold, Silke; Pelker, Bärbel (Schriften zur Südwestdeutschen Hofmusik, 2021)
In academic research, princely summer residences are regarded as places of longing, where rulers sought to realize their dream of an earthly paradise and escape the constraints of courtly ceremonial. Traditionally, this research has been based in history of art. What music was made in the summer residences, and how it might have differed from that of the main residence, has not yet been systematically studied. The conference made a contribution to this by examining the musical life at selected European summer residences of the eighteenth century and relating it to one another. The individual contributions present the respective situations of the cultivation of music at selected summer residences in the German-speaking countries as well as in Italy, Spain, England, Sweden and Russia.